Penerapan Digital Marketing pada UMKM Karya Bunda Kerupuk Ikan dan Udang di Desa Pangkalan Batang Barat - Putri Rizkiyah; Nazrantika Sunarto (Politeknik Kampar, 2025)
This Community Service program aims to analyze and implement digital marketing strategies for the Karya Bunda MSME, a fish and shrimp cracker producer in Pangkalan Batang Barat Village, Bengkalis Regency. The implementation of digital marketing is carried out as an effort to overcome limitations in conventional marketing and increase market reach. The methods used in this community service include SWOT (Strength, Weakness, Opportunities, Threats) analysis, and STP (Segmentation, Targeting, Positioning). The digital marketing strategies implemented include creating a Google My Business account, utilizing social media (Instagram, Facebook, and WhatsApp Business), preparing a content calendar, and marketing through local marketplaces. The results of the implementation of digital marketing strategies show an increase in the visibility of the Karya Bunda MSME on digital platforms, growth in interaction with consumers, and increased sales during the community service period. Obstacles faced include limited digital literacy of business owners and limited internet network, but these can be overcome through mentoring and training. This research is expected to serve as a reference and motivation for other MSMEs in developing more effective and adaptive marketing strategies for the digital era.